Bone‐muscle unit activity, salivary steroid hormones profile, and physical effort over a 3‐week stage race. Issue 1 (31st October 2013) - Grasso, D.; Corsetti, R.; Lanteri, P.; Di Bernardo, C.; Colombini, A.; Graziani, R.; Banfi, G.; Lombardi, G.
<x xml:space="preserve">Abstract</x> Muscle traction and bone metabolism are functionally linked and co‐regulated by a series of factors. Although a role for steroid hormones was hypothesized, a clear definition of the bone–muscle interconnection still lacks. To investigate this relationship, we studied bone metabolism, muscle activity, and salivary steroid hormones profile in relation with the physical effort across a cycling stage race, a model of effort in absence of load. Nine pro‐cyclists were recruited; body weight and power output/energy expenditure were recorded. Diet was kept constant. Saliva was collected at days −1, 4, 8, 12, 14, 19, and 23; blood and urine were collected at days −1, 12, and 23. Salivary steroid hormones [cortisol, dehydroepiandrosterone (DHEA), testosterone, and estradiol], serum lactate dehydrogenase (LDH), aspartate aminotransferase (AST) and creatine kinase (CK) activities, plasma sclerostin, and urinary calcium and phosphorous were measured. Cortisol remained constant, testosterone decreased at day 4, and estradiol and DHEA firstly increased and then returned to basal levels. Hormone concentrations were not correlated with plasma volume shifts. LDH, CK, AST, sclerostin, and urinary calcium and phosphorous increased. DHEA and estradiol correlated with the physical effort and the bone‐muscular markers. A relationship between muscle activity, in absence of load, and bone resorption emerged under a putative regulation by DHEA and estradiol.